Acute behavioral effects of styrene exposure: a further analysis. Issue 4 (November 1981) - Cherry, N; Rodgers, B; Venables, H; Waldron, H A; Wells, G G
Abstract : Studies were carried out on two groups to styrene-based resin. Early morning urinary mandelic acid concentrations after two days without exposure correlated with reaction time measured on arrival at work. Men were found to differ considerably in their rate of clearance of mandelic acid-those with slow reaction times. After some months at reduced exposure, a small group of men with previously high mandelic acid concentrations has speeded up on the reaction time task.